Comparison of Feeding Behaviours in Term Infants and Preterm Infants (30 To 34 Weeks) at Six Months Corrected Age - Philip, Abhishek Koshy; Kumar, KV Vijay (Journal of Nepal Paediatric Society, 2016)
Feeding is explained as the placement, manipulation and mastication of food in the oral cavity prior to initiation of the swallow. In infants, feeding is considered as innate behaviour. Literature provides evidences connecting successful feeding as a predictor for normal communication. This study aimed at comparing the feeding behaviours of term and preterm infants (30 to 34 weeks) at six months corrected age. A questionnaire was developed based on milestones on feeding development. This consisted information on mode of feeding, difficulties in feeding and feeding behaviour. The questionnaire was administered on parents of 50 infants (25 term and 25 preterm infants). Significant difference in feeding behaviour was observed between the term and preterm infants at six months of age. This long term feeding difficulty may be pronounced during the transitional feeding. Hence the need for Speech Language Pathologist to evaluate feeding behaviour at transitional period for preterm infants becomes necessary. J Nepal Paediatr Soc 2015;35(2):202-206